2018
DOI: 10.1136/bmjopen-2018-023721
|View full text |Cite
|
Sign up to set email alerts
|

Short-term outcomes after emergency surgery for complicated peptic ulcer disease from the UK National Emergency Laparotomy Audit: a cohort study

Abstract: ObjectivesThis study used national audit data to describe current management and outcomes of patients undergoing surgery for complications of peptic ulcer disease (PUD), including perforation and bleeding. It was also planned to explore factors associated with fatal outcome after surgery for perforated ulcers. These analyses were designed to provide a thorough understanding of current practice and identify potentially modifiable factors associated with outcome as targets for future quality improvement.DesignNa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 24 publications
2
23
0
2
Order By: Relevance
“…Surgical repair with closure of the perforation, with or without an omental pedicle, is the preferred treatment for PPU[ 11 , 15 , 16 ]. This repair can be achieved through either open repair or laparoscopy[ 15 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Surgical repair with closure of the perforation, with or without an omental pedicle, is the preferred treatment for PPU[ 11 , 15 , 16 ]. This repair can be achieved through either open repair or laparoscopy[ 15 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the hospital length of stay stomach PPUD, large PPUD and ACCI score were associated with increase of hospital length of stay. These findings suggest that patients who have a large stomach PPUD might need careful perioperative and postoperative personalized surgical plans as these patients may eventually undergo complicated surgical procedures [3].…”
Section: Discussionmentioning
confidence: 97%
“…Several risk factors have a potential role in developing PPUD, including cigarette smoking, NSAID (nonsteroidal anti-inflammatory drug) use, Helicobacter pylori infection, and a history of previous PUD [1]. The postoperative complications are mainly related to patients' factors rather than in-hospital care [3]. However, these risk factors and their relation to morbidity and mortality rates are not well described in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent first national study in the UK of complicated PUD requiring emergency surgery found in-hospital 60-day mortality to be higher in patients with bleeding (17.8%) than in patients with perforated PUD (11.7%),16 and yet the vast majority of complicated PUD was perforation (86%). However, a recent European study reported 90-day mortality rates to be higher for perforated PUD at 29.8% than in bleeding PUD at 5.3% 17.…”
Section: Discussionmentioning
confidence: 99%